توظيف التكنولوجيا العلمية الحديثة في مجال السياسة العقابية - صالح, م.د.رزگار عبدالكريم (Sulaimani Journal for Humanities, 2021)
The subject of electronic monitoring is considered as an innovated subject in the era of criminal justice, it represents the use of newly invented technology in punitive execution; the electronic monitoring is based on execution of punishment through an invented method outside of enclosures of panel institutions, in a free environment. This method includes an electronic system of monitoring remotely, according to which it might be certain whether someone is at a specified place of residence as per the judicial decree. Moreover, it allows the convicted person to stay at home but his/her movements are limited and monitored by a device tagged in his/her wrist or foot, which is known as electronic bracelets. This system has gained success in many developed countries that have applied it through overcoming problems resulting from execution of custodial penalties at penal institutions, which is described as a corrupted environment doesn't achieve rehabilitation of offender as a purposes of punishment rather it harms him/her socially and psychologically.